2012
DOI: 10.1109/jstsp.2012.2201693
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3-D Volumetric Probabilistic Scenes for Object Recognition

Abstract: This paper presents a new volumetric representation for categorizing objects in large-scale 3-D scenes reconstructed from image sequences. This work uses a probabilistic volumetric model (PVM) that combines the ideas of background modeling and volumetric multi-view reconstruction to handle the uncertainty inherent in the problem of reconstructing 3-D structures from 2-D images. The advantages of probabilistic modeling have been demonstrated by recent application of the PVM representation to video image registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Recently, Knopp et al [16] have shown promising results for combined segmentation and recognition. A related study on the PVM is the work in [29], where the authors propose local descriptors based on the PCA analysis and Taylor series expansion of the appearance of local neighborhoods in the PVM. These descriptors are used in Bag of Words Models for object categorization tasks and achieve adequate classification rates when using appearance information.…”
Section: Prior Work 21 3-d Object Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Knopp et al [16] have shown promising results for combined segmentation and recognition. A related study on the PVM is the work in [29], where the authors propose local descriptors based on the PCA analysis and Taylor series expansion of the appearance of local neighborhoods in the PVM. These descriptors are used in Bag of Words Models for object categorization tasks and achieve adequate classification rates when using appearance information.…”
Section: Prior Work 21 3-d Object Descriptionmentioning
confidence: 99%
“…In this realm, probabilistic volumetric methods offer a dense representation for the solution of the multi-view stereo problem, modeling explicitly the scene's uncertainty. This new representation of surface geometry [5,26] has been used in the areas of 2-d change detection [24,26], and more recently it has shown promising results in the areas of 3-d object classification [29]. Then, surface normals and shape descriptors are computed at highly likely surface locations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result gives efficient algorithm for the shape matching with the online shape retrieval and classification. Restrepo et al (2012) presented a new volumetric representation for categorizing objects in large-scale 3-D scenes reconstructed from image sequences. This algorithm presents the first work to characterize and use the local 3-D information in the scenes.…”
Section: Jcsmentioning
confidence: 99%